Green taxes and charges: Policy and practice in Britain and Germany - Stephen Smith (Institute for Fiscal Studies (IFS), 1995)
In this Commentary, the authors look at the likely effects that real year-by-year increases in road fuel duties will have on the use of cars by households and on their economic welfare, with particular attention to the distributional consequences.
Keywords: 330